2023
DOI: 10.1097/md.0000000000036698
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis of the therapeutic effect of acupuncture on dysphagia in patients with Parkinson disease

Liu Jiayu,
Wu Minmin,
Luwen Zhu

Abstract: Objective: To systematically evaluate the therapeutic effect of acupuncture on dysphagia in patients with Parkinson disease (PD). Method: We searched CNKI, WF, VIP, CBM, Cochrane Library, and Web of Chinese Biomedical Literature Randomized controlled trials on the efficacy of acupuncture in the treatment of dysphagia in patients with PD was retrieved from Science, Embase, and PubMed databases from establishment to October 2022. Outcome indicators includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 20 publications
(42 reference statements)
0
0
0
Order By: Relevance
“…Acupuncture at scalp acupoints dredges the meridians, regulates qi and blood, and balances the zang-fu organs. Previous studies have reported that scalp acupuncture produced a rapid and effective clinical result on the vertigo symptoms of middle-aged and elderly patients with cervical spondylosis of the vertebral artery type, which improved their symptoms of neck pain and vertigo[ 24 ]. The scalp acupuncture of Lingnan flying acupuncture therapy effectively relieves the vertigo symptoms and blood supply of posterior circulation in patients[ 25 ].…”
Section: Resultsmentioning
confidence: 99%
“…Acupuncture at scalp acupoints dredges the meridians, regulates qi and blood, and balances the zang-fu organs. Previous studies have reported that scalp acupuncture produced a rapid and effective clinical result on the vertigo symptoms of middle-aged and elderly patients with cervical spondylosis of the vertebral artery type, which improved their symptoms of neck pain and vertigo[ 24 ]. The scalp acupuncture of Lingnan flying acupuncture therapy effectively relieves the vertigo symptoms and blood supply of posterior circulation in patients[ 25 ].…”
Section: Resultsmentioning
confidence: 99%